2018
DOI: 10.1111/trf.15089
|View full text |Cite
|
Sign up to set email alerts
|

A whole genome approach for discovering the genetic basis of blood group antigens: independent confirmation for P1 and Xga

Abstract: BACKGROUND Although P1 and Xga are known to be associated with the A4GALT and XG genes, respectively, the genetic basis of antigen expression has been elusive. Recent reports link both P1 and Xga expression with nucleotide changes in the promotor regions and with antigen‐negative phenotypes due to disruption of transcription factor binding. STUDY DESIGN AND METHODS Whole genome sequencing was performed on 113 individuals as part of the MedSeq Project with serologic RBC antigen typing for P1 (n = 77) and Xga (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Moreover, two other SNVs (rs2143918 and rs5751348), which are tightly linked to rs8138197, showed 100% correlation with P1 expression in different populations 20‐22 . In agreement with the aforementioned studies, it was recently reported that four SNVs (rs66781836, rs8138197, rs2143918 and rs5751348) correlated with P 1 and P 2 phenotypes 21 . Studies examining the gene regulation of those SNVs showed that rs5751348 contains potential transcription factor‐binding sites for runt‐related transcription factor 1 (RUNX1) and early growth response 1 (EGR1), suggesting that these proteins play a role in creating P 1 and P 2 phenotypes 22,23 …”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Moreover, two other SNVs (rs2143918 and rs5751348), which are tightly linked to rs8138197, showed 100% correlation with P1 expression in different populations 20‐22 . In agreement with the aforementioned studies, it was recently reported that four SNVs (rs66781836, rs8138197, rs2143918 and rs5751348) correlated with P 1 and P 2 phenotypes 21 . Studies examining the gene regulation of those SNVs showed that rs5751348 contains potential transcription factor‐binding sites for runt‐related transcription factor 1 (RUNX1) and early growth response 1 (EGR1), suggesting that these proteins play a role in creating P 1 and P 2 phenotypes 22,23 …”
Section: Introductionsupporting
confidence: 79%
“…Previous studies have found that a single‐nucleotide variant (SNV) in A4GALT (rs8138197) correlated with P1 expression in 99.5% and 100% of Swedish 18 and Taiwanese 19 blood donors, respectively. Moreover, two other SNVs (rs2143918 and rs5751348), which are tightly linked to rs8138197, showed 100% correlation with P1 expression in different populations 20‐22 . In agreement with the aforementioned studies, it was recently reported that four SNVs (rs66781836, rs8138197, rs2143918 and rs5751348) correlated with P 1 and P 2 phenotypes 21 .…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…We estimated the effect of this limitation on RBC and PLT antigen typing by reviewing the antigen allele tables for nonexonic nucleotide changes that impact antigen phenotype predictions. Other than the recently published transcription factor binding regions deep within A4GALT1 Intron 1 and upstream of XG that control the expression the P1 and Xg a antigens , all other nonexonic changes associated with antigenic variation are located within 13 bp of an exon boundary. In fact, analysis of WES data from all 75 participants showed a similar depth of coverage pattern to previous WGS efforts, with overall adequate sequencing coverage of all exons, but with some low‐sequence coverage regions in nonantigen allele nucleotide positions within CR1 , C4A , C4B , and several other genes (Fig.…”
Section: Resultsmentioning
confidence: 99%